The first experience of using beta-hydroxybutyrate analysis of capillary blood in the diagnosis of non-diabetic hypoglycemia in adults - M. Yu. Yukina; E. A. Troshina; N. F. Nuralieva; N. G. Mokrysheva (Ожирение и метаболизм, 2022)
Background: The diagnostic threshold of β-hydroxybutyrate (BHB) at the moment of hypoglycemia in insulinoma was developed for venous blood many years ago, when there were no alternative ways to measure ketones. Number of works, mainly on patients with diabetes mellitus, found differences in the measurement of this indicator in venous and capillary blood, but the results were contradictory. Moreover, this study was not previously used in the diagnosis of non-diabetic hypoglycemia (NDH) in adults on the territory of the Russian Federation.Aim: To estimate the effectiveness of the method for determining BHB in capillary blood and its place in the diagnosis of NDH.Materials and methods: We conducted an experimental, cross-sectional, comparative study and included patients with suspected NDH who underwent a standard fast test. The BHB level in capillary blood was determined every 6 hours during the fast test and at its completion.Results: Based on the results of the fast test, the participants (n=154) were divided into groups: with hyperinsulinemic variant of NDH and IFRoma (n=98; group 1), with hypoinsulinemic variant of NDH /absence of NDH (n=56; group 2). When comparing the level of BHB at the moment of fasting completion, significant differences were obtained between groups 1 and 2 (p<0.001). According to the ROC analysis, the determination of BHB for differentiation the hyper- and hypoinsulinemic variants of hypoglycemia is characterized by excellent quality of model (AUC=99,1% [98,0%; 100,0%]). The BHB determination in capillary blood has the maximum diagnostic accuracy at a cut-off point of ≤ 1.4 mmol/L (Se 98.0%, Sp 96.4%, PPV 98.0%, NPV 96.4%, Ac 97.4%). Exceeding the diagnostic threshold of BHB was first recorded after 24h of fasting; at the same point, a significant difference was determined when comparing BHB indicators between two consecutive measurements (between 18h and 24h).Conclusion: The BHB determination in capillary blood is a highly sensitive and highly specific additional method for the differential diagnosis of NDH variants. The diagnostic threshold for BHB of capillary blood, which allows differentiating hyper- and hypoketonemic variants of NDH, is ≤1.4 mmol / L. It is advisable to initiate control of BHB in the blood no earlier than 18 hours after the start of the fast test.